Constraints on Formulary Design Under the Affordable Care Act. (24th February 2017) - Andersen, Martin
Summary: I study the effect of prescription drug essential health benefits (EHB) requirements from the Affordable Care Act on prescription drug formularies of health insurance marketplace plans. The EHB regulates the number of drugs covered but leaves other dimensions (cost sharing and utilization management) of the formulary unregulated. Using data on almost all formularies in the country, I demonstrate that requiring insurers to cover one additional drug adds 0.22 drugs (3.3%) to the average formulary, mostly owing to firms increasing the number of drugs covered to comply with the EHB requirement. The EHB requirement also increases the probability that a drug is subject to utilization management and is assigned to a higher (more costly) formulary tier. My results suggest that newly covered drugs are 22.3 percentage points more likely to be subject to utilization management, compared to 36.7% for the average covered drug. Using formularies for Medicare Advantage plans, which are subject to uniform, nationwide benefit design standards, and the formulary status of newly approved drugs that do not satisfy the EHB requirement, I reject the hypotheses that consumer demand or effects on plan entry can explain my results. Copyright © 2017 John Wiley & Sons, Ltd.